2010
DOI: 10.1590/s1519-69842010000100028
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and experimental infection with Vibrio alginolyticus in the sea horse, Hippocampus reidi Ginsburg, 1933 (Osteichthyes: Syngnathidae) in Brazil

Abstract: The aim of this study was to evaluate the pathogenicity of Vibrio alginolyticus isolated from an outbreak of sea horse Hippocampus reidi reared in the State of Santa Catarina, Brazil, by experimental infection. Sea horses with necrosis on the mouth epithelium were collected from aquaria at the Aquaculture Department, UFSC and the bacterium isolated from the mouth, liver, heart and blood in tiosulphate citrate bilesalt sucrose agar broth. The strains were identified by API 20E kit with 99.1% probability as Vibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…Some other Vibrio species have been identified in seahorses, for example V. alginolyticus in H. reidi , H. guttulatus and H. hippocampus (Balcázar ; Martins et al . ), V. splendidus in H. guttulatus and H. hippocampus (Balcázar et al . ), V. harveyi in H. kuda (Alcaide et al .…”
Section: Number Of Deaths and Mortality Of The Seahorses Hippocampus mentioning
confidence: 99%
“…Some other Vibrio species have been identified in seahorses, for example V. alginolyticus in H. reidi , H. guttulatus and H. hippocampus (Balcázar ; Martins et al . ), V. splendidus in H. guttulatus and H. hippocampus (Balcázar et al . ), V. harveyi in H. kuda (Alcaide et al .…”
Section: Number Of Deaths and Mortality Of The Seahorses Hippocampus mentioning
confidence: 99%
“…Other Vibrio such as Vibrio alginolyticus , Vibrio harveyi , Vibrio hippocampi sp. nov., V. parahemolyticus , and Vibrio splendidus have been found to be pathogens in Hippocampus guttulatus , Hippocampus hippocampus , H. kelloggi , H. kuda , and Hippocampus reidi (Alcaide et al ; Tendencia ; Yang et al ; Balcázar et al ; Martins et al ; Raj et al ). Together with the previous studies, this finding indicated that the intestinal bacteria of Vibrio , especially the V. parahaemolyticus strain CM12 may be the most important pathogen of intestinal diseases in the cultured seahorses H. trimaculatus .…”
Section: Resultsmentioning
confidence: 99%
“…Vibriosis in seahorses has been previously reported, but all were involved in the experimental breeding or aquariums, and several Vibrio species including V. alginolyticus (Martins et al . ), V. splendidus (Balcazar et al . ) and V. fortis (Wang et al .…”
Section: Mortality and Food Intake Of The Lined Seahorses Hippocampusmentioning
confidence: 99%